Heme oxygenase 1 confers gilteritinib resistance in FLT3-ITD acute myeloid leukemia in a STAT6-dependent manner - Tianzhuo Zhang; Danna Wei; Yun Zhan; Zhengmei Long; Tingting Lu; Peng Zhao; Rui Gao; Qian Kang; Luxin Zhang; Min Liu; Xueying Yang; Jishi Wang (Cancer Cell International)
Abstract Background Acute myeloid leukemia (AML) is the most common type of acute leukemia in adults. We previously discovered that heme oxygenase 1 (HO1) is crucial for chemoresistance in AML, but the detailed molecular mechanism of that remains unclear. Methods RNA sequencing was conducted to assess transcriptomic changes in three pairs of AML cells after regulating the expression of HO1. The molecular mechanism by which HO1 induces gilteritinib resistance in FLT3-ITD (FMS-like tyrosine kinase 3 (FLT3) internal tandem duplication (ITD)) AML was evaluated by quantitative real-time PCR (qRT-PCR), CCK-8, flow cytometry, and western blotting. FLT3-ITD AML mouse models were established to investigate the effects of HO1 expression on gilteritinib resistance in vivo. Results In these three pairs of AML cells, we discovered that HO1-mediated drug resistance is connected to the interleukin-4-mediated signaling pathway (specifically STAT6) only in MV4-11 cells with the FLT3-ITD mutation. Further findings revealed that HO1 overexpression confers gilteritinib resistance in FLT3-ITD AML cell lines and primary individual specimens. While suppression of HO1 sensitized FLT3-ITD AML cell lines and primary individual specimens to gilteritinib. Mechanistically, western blotting and flow cytometry confirmed that HO1-mediated gilteritinib resistance is related to STAT6 phosphorylation in FLT3-ITD AML cell lines and primary individual specimens. Moreover, tumor-bearing mice were employed to determine that HO1 overexpression conferred gilteritinib resistance in vivo. Conclusions Collectively, these studies illustrate that HO1 may act as a successful treatment target for gilteritinib-resistant FLT3-ITD AML patients.